Solving the Internet jurisdiction puzzle - Svantesson, Dan Jerker B. (Oxford : Oxford University Press, 2017)
This text deals with the topic of Internet jurisdiction, and why territoriality is not suitable in determining this area. Svantesson surveys possible solutions advanced in the area of Internet jurisdiction, as well as assessing the new proposals for law reform that demand a paradigm shift in relation to jurisdiction.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 16, 2017).
Keywords: Internet -- Law and legislation; Jurisdiction; Law; Laws of specific jurisdictions & specific areas of law